PATHOMORPHOLOGICAL CHANGES IN THE STRUCTURAL COMPONENTS OF PANCREATIC TISSUE IN THE OFFSPRING OF DIABETIC MOTHER RATS (LITERATURE REVIEW) - Adilbekova D.B., Erkinova M.U., Erkinova Z.U., Odilova S.B., Rayimkulova Z.I., Sharipova U.N., (Central Asian Journal of Medicine, 2025)
In recent years, diabetes mellitus has become a widespread endocrine disorder and a significant medical and social problem for many countries. This is often associated with the high frequency of various complications of the disease (blindness, small intestine insufficiency, myocardial infarction, gastrointestinal system disorders, gangrene of the limbs, etc.). These complications, in turn, lead to loss of working capacity and disability in patients. Although damage to various organs in diabetes mellitus has been extensively studied, unfortunately, the morphofunctional condition of organs, particularly the vascular and tissue structures of the stomach, has not yet been sufficiently explored in depth. To date, the morphofunctional features and pathogenesis mechanisms of organ damage in diabetes mellitus, especially the ante- and postnatal morphogenesis of internal organs and the pathomorphological mechanisms of damage in offspring born to diabetic mothers, have not been adequately investigated. However, an in-depth study of this disease opens up opportunities to influence the outcome of complications, and to improve the quality and effectiveness of treatment.Thus, the search for solutions to these issues highlights the relevance and significance of problems in this field.